2017
DOI: 10.3384/ecp17144214
|View full text |Cite
|
Sign up to set email alerts
|

Study of Energy Losses in Digital Hydraulic Multi-Pressure Actuator

Abstract: A digital hydraulic multi-pressure actuator is a new actuator concept, which aims at lowering energy losses and decreasing dynamic requirements of a prime mover in mobile hydraulic applications. The actuator consists of an integrated hydraulic accumulator, which serves as an energy storage and a number of asymmetric cylinders acting as discrete pressure transformers. Leak-free on/off-valves are used to direct flow from the discrete pressure transformers to the actuator. Input power is supplied by charging the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 5 publications
(6 reference statements)
1
8
0
Order By: Relevance
“…When compared to the alternative controller used by Huova et al, 16 it can be concluded that the new controller does not improve energy efficiency or the force tracking performance. This is somewhat conflicting result, because faster valves and more advanced control algorithm were used.…”
Section: Resultsmentioning
confidence: 83%
See 4 more Smart Citations
“…When compared to the alternative controller used by Huova et al, 16 it can be concluded that the new controller does not improve energy efficiency or the force tracking performance. This is somewhat conflicting result, because faster valves and more advanced control algorithm were used.…”
Section: Resultsmentioning
confidence: 83%
“…The exact values of the dead volumes and the bulk modulus of hose were not known but the values were used by the controller, and for analysis and simulations. The boom length was 4 m and the exact dimensions of the boom mechanism were given by Huova et al 16 Linear potentiometers were used to measure the positions of the main cylinder and converter cylinders. The control hardware consisted of a dSPACE DS1006 controller board together with a DS2002 ADC board, a DS3001 incremental encoder board, and a DS4302 CAN interface board.…”
Section: Position Controllermentioning
confidence: 99%
See 3 more Smart Citations